Metabolite Profile of Alzheimer’s Disease in the Frontal Cortex as Analyzed by HRMAS 1H NMR - Zhang, Yuzhong; Liu, Zhou; Ji, Bing; Liu, Lijian; Wu, Shaoxiong; Liu, Xiaowu; Wang, Silun; Wang, Liya (Frontiers in Aging Neuroscience, 2019)
Background: Investigation on neurochemical changes in the frontal cortex in individuals with Alzheimer’s disease (AD) and different Apolipoprotein E (APOE) genotypes using ex vivo solid-state high-resolution NMR analysis may lead to better understanding on neurochemistry associated to AD and new AD-specific metabolite biomarkers that might potentially improve the clinical diagnosis of AD. Methods: Intact tissue samples of the frontal cortex were obtained from 11 patients and 11 age-matched non-demented controls. Metabolite profiles in all samples were analyzed ex vivo using solid-state high-resolution magic angle spinning (HRMAS) 600 MHz 1H nuclear magnetic resonance (NMR). Logistic regression analysis was used to rank metabolites based on their level of contribution in differentiating AD patients and controls, and different AD-associated APOE genotypes (APOE 4 vs. APOE 3). Results: Tissue samples from AD patients showed significantly lower NAA/Cr (p = 0.011), Ace/Cr (p = 0.027), GABA/Cr (p = 0.005), Asp/Cr (p < 0.0001), mI/Cr (p < 0.0001), and Tau/Cr (p = 0.021), and higher PCho/Cr (p < 0.0001), GPCho/Cr (p < 0.0001), and α&β-Glc/Cr (p < 0.0001) than did controls. Specifically, a newly observed resonance at 3.71 ppm, referred to as α&β-Glc, was observed in 90.9% of AD samples (10/11). Samples with APOE 4 also exhibited higher PCho/Cr (p = 0.0002), GPCho/Cr (p = 0.0001), α&β-Glc/Cr (p < 0.0001), and lower Asp/Cr (p = 0.004) and GABA/Cr (p = 0.04) than samples with APOE 3. In the logistic regression analysis, PCho, GPCho, ASP, and α&β-Glc were found to be the most relevant metabolites for differentiating AD patients and controls, and different APOE genotypes. Conclusions: HRMAS 1H NMR with high spectral resolution and sensitivity offers a powerful tool for gaining quantitative information on AD associated neurochemical changes. There are important neurochemical differences in the frontal cortex between AD patients and controls, and between those with different APOE genotypes. The resonance (α&β-Glc) found at 3.71 ppm in AD patients may be further investigated for its potential in diagnosis and monitoring of AD.